Ethnic Employees' Behaviour Vis-a-Vis Customers in the Service Sector - Peter Nijkamp; Mediha Sahin; Marius Rietdijk (European Regional Science Association (ERSA), 2006)
Our age is the age of migration. The socio-economic position of ethnic groups in a globally mobile society has extensively been studied in recent years, from the perspective of their skills, language abilities, adjustment behaviour, and so forth. This study investigates the social and economic performance of ethnic groups in cities by addressing the question whether these groups have a higher or lower reputation or esteem on the labour market than their indigenous equals, seen from the perspective of the customer's perception and satisfaction. There is a popular feeling that ethnic employees in the service sector are less client-centered than indigenous employees. Sometimes, stigmatization is mentioned as a factor that acts as a negative predictor for someone's position on the job market. This phenomenon calls for a careful and critical assessment, as it may also rest on an unjustified stigma. Therefore, it is an interesting research question whether workers of ethnic origin, e.g., in the service sector are more or less client-friendly than others. How do others judge their social or economic performance? After an extensive literature review, we formulate several hypotheses on the actual behaviour of ethnic employees and test these on the basis of empirical fieldwork in the service sector – notably in the retail sector – in the city of Amsterdam. Our conclusion is that in general there is no ethnic bias in the behaviour of these employees, although our findings suggest that gender bias does occur.
Keywords: 330